Geographic variation in fitness‐related traits of the bladderwrack Fucus vesiculosus along the Baltic Sea‐North Sea salinity gradient. Issue 16 (23rd July 2019) - Barboza, Francisco R.; Kotta, Jonne; Weinberger, Florian; Jormalainen, Veijo; Kraufvelin, Patrik; Molis, Markus; Schubert, Hendrik; Pavia, Henrik; Nylund, Göran M.; Kautsky, Lena; Schagerström, Ellen; Rickert, Esther; et al.
Abstract: In the course of the ongoing global intensification and diversification of human pressures, the study of variation patterns of biological traits along environmental gradients can provide relevant information on the performance of species under shifting conditions. The pronounced salinity gradient, co‐occurrence of multiple stressors, and accelerated rates of change make the Baltic Sea and its transition to North Sea a suitable region for this type of study. Focusing on the bladderwrack Fucus vesiculosus, one of the main foundation species on hard‐bottoms of the Baltic Sea, we analyzed the phenotypic variation among populations occurring along 2, 000 km of coasts subjected to salinities from 4 to >30 and a variety of other stressors. Morphological and biochemical traits, including palatability for grazers, were recorded at 20 stations along the Baltic Sea and four stations in the North Sea. We evaluated in a common modeling framework the relative contribution of multiple environmental drivers to the observed trait patterns. Salinity was the main and, in some cases, the only environmental driver of the geographic trait variation in F. vesiculosus . The decrease in salinity from North Sea to Baltic Sea stations was accompanied by a decline in thallus size, photosynthetic pigments, and energy storage compounds, and affected the interaction of the alga with herbivores and epibiota. For some traits, drivers that vary locally such as wave exposure, light availability or nutrient enrichment were also important. The strong genetic population structure in this macroalgae might play a role in the generation and maintenance of phenotypic patterns across geographic scales. In light of our results, the desalination process projected for the Baltic Sea could have detrimental impacts on F. vesiculosus in areas close to its tolerance limit, affecting ecosystem functions such as habitat formation, primary production, and food supply. Abstract : In the course of the ongoing global change, the study of variation patterns of biological traits along environmental gradients can provide relevant information on the performance of species under shifting conditions. Focusing on the bladderwrack Fucus vesiculosus, one of the main foundation species on hard‐bottoms of the Baltic Sea, we analyzed the phenotypic variation among populations occurring along 2, 000 km of coasts. The decrease in salinity from North Sea to Baltic Sea stations was accompanied by a decline in thallus size, photosynthetic pigments and energy storage compounds, and affected the interaction of the alga with herbivores and epibiota. In light of our results, the desalination process projected for the Baltic Sea could have detrimental impacts on the phenotype of F. vesiculosus, affecting ecosystem functions such as habitat formation, primary production and food supply.